Economic evaluation of pay-for-performance in health care: a systematic review. - Emmert, Martin; Eijkenaar, Frank; Kemter, Heike; Esslinger, Adelheid Susanne; Schöffski, Oliver (European Journal of Health Economics, 2012)
<h4 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Background <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec1" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Pay-for-performance (P4P) intents to stimulate both more effective and more efficient health care delivery. To date, evidence on whether P4P itself is an efficient method has not been systematically analyzed. <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Objective <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec2" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> To identify and analyze the existing literature regarding economic evaluation of P4P. <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Data sources <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec3" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> English, German, Spanish, and Turkish language literature were searched in the following databases: Business Source Complete, the Cochrane Library, Econlit, ISI web of knowledge, Medline (via PubMed), and PsycInfo (January 2000–April 2010). <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Study selection <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec4" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Articles published in peer-reviewed journals and describing economic evaluations of P4P initiatives. Full economic evaluations, considering costs and consequences of the P4P intervention simultaneously, were the prime focus. Additionally, comparative partial evaluations were included if costs were described and the study allows for an assessment of consequences. Both experimental and observational studies were considered. <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Results <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec5" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> In total, nine studies could be identified. Three studies could be regarded as full economic evaluations, and six studies were classified as partial economic evaluations. Based on the full economic evaluations, P4P efficiency could not be demonstrated. Partial economic evaluations showed mixed results, but several flaws limit their significance. Ranges of costs and consequences were typically narrow, and programs differed considerably in design. Methodological quality assessment showed scores between 32% and 65%. <h3 class="Heading" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: 400; font-stretch: inherit; font-size: 1.2em; line-height: inherit; font-family: inherit; margin: 0.7em 0px 0.3em; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> Conclusion <h2 class="Heading" style="border: 0px; font-weight: 400; font-stretch: inherit; font-size: 24px; line-height: 1.2; font-family: Georgia, 'New Century Schoolbook', 'Nimbus Roman No9 L', serif; margin: 7px 0px; padding: 0px; vertical-align: baseline; outline: 0px; letter-spacing: 0.02em; width: 580px; color: rgb(51, 51, 51);">   <div class="AbstractSection" id="ASec6" style="border: 0px; font-stretch: inherit; font-size: 13px; line-height: 13px; font-family: 'Helvetica Neue', Arial, Helvetica, sans-serif; margin: 0.3em 0px 0px; padding: 0px; vertical-align: baseline; outline: 0px;"> <p class="Para" style="border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: inherit; line-height: 1.6; font-family: inherit; margin: 0px; padding: 0px; vertical-align: baseline; outline: 0px; width: 580px;"> The results show that evidence on the efficiency of P4P is scarce and inconclusive. P4P efficiency could not be demonstrated. The small number and variability of included studies limit the strength of our conclusions. More research addressing P4P efficiency is needed.
WiSo-Import:2015-03-26:4185
Keywords: Cost-effectiveness; Economic evaluation; Efficiency; P4P; Pay-for-performance; ROI